THE EMERGENCE OF A NEW VIRUS CALLED COVID-19, BOTH IN THE WORLD AND IN INDONESIA MAKES ALL ELEMENTS OF SOCIETY FEEL DIFFICULT. THE PANDEMIC THAT HAS BEEN GOING ON SINCE MARCH 2020 IN INDONESIA IS STILL NOT OVER UNTIL NOW. HOWEVER, THERE IS ONE ALTERNATIVE SOLUTION THAT CAN BE DONE TO HELP TACKLE THE PANDEMIC, NAMELY BY MODELING THE SPREAD OF COVID-19 TO PROVIDE AN OVERVIEW FOR THE PUBLIC AND GOVERNMENT SO THEY CAN TAKE FURTHER ACTION. ONE OF THE KNOWN EPIDEMIC MODELING IS SIR MODELING, WHICH IS A MODEL THAT DIVIDES INDIVIDUALS INTO CERTAIN GROUPS/COMPARTMENTS. IN THIS FINAL PROJECT, THE SIR MODEL AND ONE OF ITS DERIVATIVES, NAMELY SIR-D, WAS DEVELOPED WITH THE HELP OF THE MACHINE LEARNING CONCEPT TO ANALYZE AND SIMULATE SEVERAL SCENARIOS OF THE SPREAD OF A PANDEMIC. THERE ARE 3 SIMULATION SCENARIOS MADE, THE SCENARIO WITHOUT THE IMPACT OF VACCINATION, THE SCENARIO WITH THE IMPACT OF VACCINATION, AND THE SCENARIO OF VACCINATION WITHOUT BEING ACCOMPANIED BY A STRICT HEALTH PROTOCOL. THE SIMULATIONS OF THE TWO MODELS SHOWED THAT THE VACCINATION PROCESS HAD AN IMPACT ON REDUCING THE SPREAD OF COVID-19, ALTHOUGH IT WAS LESS SIGNIFICANT DUE TO THE INCOMPLETE VACCINATION PROCESS. MEANWHILE, IF THE VACCINATION PROCESS IS NOT CARRIED OUT WITH HEALTH PROTOCOLS, THE RESULT WILL BE THAT THE SPREAD OF THE PANDEMIC WILL SOAR AND FORM THE SECOND WAVE IN INDONESIA. THIS MAKES THE IMPACT AND THE VACCINATION PROCESS FUTILE. THIS MEANS THAT THE VACCINATION PROCESS CANNOT BE UNDERESTIMATED AND THE PUBLIC MUST CONTINUE TO ADHERE TO APPLICABLE HEALTH PROTOCOLS. IN GENERAL, IT CAN BE CONCLUDED THAT THE EPIDEMIOLOGICAL MODEL USED CAN PROVIDE AN OVERVIEW OF THE SIMULATION WITH A DEGREE OF ACCURACY WHEN MEASURED BY THE MAPE METRIC, NAMELY THE SIR MODEL OF 0.41198 AND THE SIR-D MODEL OF 0.01712. - Petra Natanael, David
The emergence of a new virus called COVID-19, both in the world and in Indonesia makes all elements of society feel difficult. The pandemic that has been going on since March 2020 in Indonesia is still not over until now. However, there is one alternative solution that can be done to help tackle the pandemic, namely by modeling the spread of COVID-19 to provide an overview for the public and government so they can take further action. One of the known epidemic modeling is SIR modeling, which is a model that divides individuals into certain groups/compartments. In this final project, the SIR model and one of its derivatives, namely SIR-D, was developed with the help of the machine learning concept to analyze and simulate several scenarios of the spread of a pandemic. There are 3 simulation scenarios made, the scenario without the impact of vaccination, the scenario with the impact of vaccination, and the scenario of vaccination without being accompanied by a strict health protocol. The simulations of the two models showed that the vaccination process had an impact on reducing the spread of COVID-19, although it was less significant due to the incomplete vaccination process. Meanwhile, if the vaccination process is not carried out with health protocols, the result will be that the spread of the pandemic will soar and form the second wave in Indonesia. This makes the impact and the vaccination process futile. This means that the vaccination process cannot be underestimated and the public must continue to adhere to applicable health protocols. In general, it can be concluded that the epidemiological model used can provide an overview of the simulation with a degree of accuracy when measured by the MAPE metric, namely the SIR model of 0.41198 and the SIR-D model of 0.01712.